ANALISIS PEMBATALAN MEREK SUPERMAN YANG MEMILIKI PERSAMAAN PADA KESELURUHANNYA MENURUT UU NOMOR 20 TAHUN 2016 (STUDI PUTUSAN NOMOR 1105K/PDT.SUS-HKI/2018) - Jeri Irawan; Simona Bustani (Jurnal Hukum Adigama, 2020)
Indonesia is a state of law, where every citizen, both Indonesian citizens and foreign nationals living in Indonesia, must obey the laws that are regulated in Indonesia. Trademark is one of the intellectual property rights regulated in the Indonesia Reguliation Trademark. because the brand is something that is often used in the world of commerce in Indonesia. Based on the Indonesia regulation Trademark, is a sign that can be displayed graphically both in terms of images, logos, names, words, or letters, which are used as a differentiator of various types of goods and / or services produced by individuals or legal entities in the trading of goods and / or services. In trading, brands that have similarities in principle or as a whole are often encountered. The purpose of this study is to find a picture of brand rejection that has similarities in its entirety. The method used in this study is a normative approach. The results of this study illustrate the legal liability of a brand examiner that has similarities in principle if a trademark dispute occurs.